Hubungan Self Efficacy dan Self Care Management dengan Tingkat Kepatuhan Minum Obat pada Penderita Hipertensi di RSUD Kecamatan Mandau Riau - Salsabila Nitya; Cut Mourisa (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Hypertension is a primary risk factor for cardiovascular diseases, including stroke, coronary artery disease, atrial fibrillation, and peripheral vascular disease. Often referred to as "The Silent Killer," its onset is frequently asymptomatic, making early detection challenging. Effective interventions, both pharmacological and non-pharmacological, are necessary to manage hypertension and reduce complications. Long-term treatment requires adherence to prescribed medications, with self-care management playing a vital role in minimizing hypertension's adverse effects. Self-efficacy, or an individual's belief in their abilities, is crucial for improving medication adherence and self-care activities. This study aimed to examine the correlation between self-efficacy and self-care management in relation to medication adherence among hypertension patients at RSUD Mandau District. A non-experimental, quantitative, analytic correlation study with a cross-sectional design was conducted, involving 38 hypertension patients. Self-efficacy was measured using the MASES-R (Medication Adherence Self-Efficacy Scale-Revision), medication adherence was assessed with the MMAS-8 (8-item Morisky Medication Adherence Scale), and self-care management was evaluated using the HBP-SCP (Hypertension Self-Care Profile). The findings revealed a significant correlation between self-efficacy and medication adherence (p=0.000, r=0.594). Additionally, self-care management was significantly correlated with medication adherence (p=0.027, r=0.360). In conclusion, self-efficacy and self-care management both significantly correlate with medication adherence in hypertension patients at RSUD Mandau District.